질산염 화합물 함유 식물 추출물이 in vitro 반추위 발효성상과 메탄 발생에 미치는 영향 - 이신자; 이수경; 김민성; 이성실; Shin Ja Lee; Su Kyoung Lee; Min Sung Kim; Sung Sill Lee (농업생명과학연구, 2016)
본 시험은 질산염함유 식물 추출물을 이용하여 in vitro 반추위 발효성상 및 반추위 메탄 발생에 미 치는 영향을 알아보기 위해 수행되었다. 공시재료는 감자, 당근, 배추, 상추 및 시금치 추출물을 사용하 였으며, 발효 기질은 2mm로 분쇄된 timothy 0.3g을 사용하였다. In vitro 실험은 조사료(timothy) 및 배합사료를 6:4의 비율로 급여한 반추위 cannnula가 시술된 한우 암소에서 채취하였다. 반추위액과 McDougall’s buffer를 1:2의 비율로 혼합한 발효액을 0.3g timothy와 식물 추출물이 담긴 50mL serum bottle에 혐기상태로 20mL 분주한 뒤, 39℃에서 9, 12, 24, 48시간 동안 발효하였다. pH는 발 효 시간이 증가함에 따라 점점 감소하며, 6.31~6.96으로 정상범위였다. 건물 소화율은 9시간 배추 추 출물구에서 유의적으로 낮았고, 암모니아 농도는 감자, 배추, 상추 추출물구에서 대조구에 비해 첨가구 에서 유의적으로(p<0.05) 낮았으며, 반추위 미생물 성장량은 발효 24시간대의 당근 추출물구에서 높았 다(p<0.05). Acetate와 propionate 농도는 대조구에 비해 첨가구에서 유의적으로 낮았으며(p<0.05) butyrate 농도는 첨가구간에 발효시간별로 각각 다른 양상을 보였다. 총 가스 발생량은 발효 12시간 및 24시간대에서 배추, 상추, 시금치 추출물구에서 유의적으로(p<0.05) 낮았으며, 메탄 발생량은 감자, 배 추, 시금치 추출물구가 대조구에 비해 유의적으로(p<0.05) 낮았고, 이산화탄소 발생량 또한 첨가구에 비해 대조구에서 유의적으로(p<0.05) 낮았다. 결과적으로 본 시험에 사용된 5종의 질산염 함유 식물 추 출물은 반추위 발효에 악영향을 미치지 않으면서 메탄저감 효과를 나타내었다. 특히 배추 추출물은 반 추위내 메탄발생을 저감시킬 수 있는 식물추출물로서 가능성이 높은 것으로 사료된다. This study was conducted to evaluate the effects of nitrate-rich plants extracts on the in vitro rumen fermentation characteristics and rumen methane production. The extracts of nitrate-rich plants, as potato, carrot, chinese cabbage, lettuce and spinach were used in this study. The ruminal fluid was collected from a cannulated Hanwoo cow fed concentrate and timothy in the ratio of 6 to 4. The 20mL of mixture, comparing McDougall’s buffer and rumen fluid in the ratio 2 to 1, was dispensed anaerobically 50mL serum bottles containing 0.3g of timothy substrate and extracts of nitrogen-rich plants. The serum bottles were incubated 39℃ for 9, 12, 24, 48 hours. The pH value was decreased by increased incubation times and normal range to 6.31 to 6.96. The dry matter digestibility was significantly(p<0.05) lower in chinese cabbage than in control at 9h incubation time. Ammonia concentration was significantly(p<0.05) lower in potato, chinese cabbage, lettuce than in control and the rumen microbial growth rate was significantly(p<0.05) higher in carrot than in control at 24h incubation time. The concentrations of acetate and propionate was significantly(p<0.05) lower in treatment than in control. The concentration of butyrate was showed a different pattern depending on treatments. Total gas emissions was significantly(p<0.05) lower in chinese cabbage, lettuce, spinach than in control at 12h, 24h incubation time. Methane production was significantly(p<0.05) lower in potato, chinese cabbage, spinach than in control, carbon dioxide production was significantly(p<0.05) lower in treatment than in control. In conclusion, supplementation of the nitrate-rich plant extracts in ruminal fermentation in vitro resulted in decreasing the methane production without adversely affecting the fermentation characteristics. Particularly the chinese cabbage extract was regard as a potential candidate for reducing the methane emission in ruminants.